Immunohistological Diagnosis of Primary and Metastatic Renal Cell Carcinoma Using Panel of Immunohistochemical Markers: A Single Centre Study - Dhanetwal, Murari Lal; Badwal, Sonia; Gahlot, Gaurav Pratap Singh; Sahai, Kavita; Shukla, A K (Annals of Pathology and Laboratory Medicine, 2019)
Background: Tumour heterogeneity and lack of markers with high specificity makes diagnosis of renal cell carcinoma (RCC) challenging. The study was undertaken to evaluate panel of IHC markers to enable diagnosis and reproducible classification in primary and metastatic renal tumors. Methods: Descriptive Study wherein 100 cases of RCC and 25 trucut biopsies (20 metastatic and 5 primary renal tumors) were evaluated for morphology and immunostained by panel of immunohistochemical (IHC) markers consisting of CA-9, CD10, CK-7, AMACAR and TFE-3 with additional markers as required. Result: Morphologically tumors were grouped as clear cell and nonclear cell (eosinophilic and poorly differentiated). Clear cell RCCs (CCRCC), clear cell papillary RCC (CCPRCC) and multilocular cystic RCC (MCRNLMP) displayed strong statistical association of CA-9 immunostaining (p=50.00, x2-0.000). Inverse correlation was found between the intensity of the staining of CA-9 and tumor grade. (p=32.97, x2=0.000). CA-9 and CK-7 co-expression was evident in all cases of CCPRCC and MCRNLMP. Papillary RCC exhibited positive statistical correlation with CK-7 and AMACAR. E-cadherin and CD117 were required additionally to differentiate between oncocytoma and chromophobe RCC. CD10 and Pax 8 were most helpful in diagnosing metastatic RCCs Conclusion: IHC panel consisting of CA-9, CD10, CK7, AMACR and TFE3 helps triage RCCs with clear cell/eosinophilic cell / papillary/poorly differentiated pattern. In a setting of metastatic RCC, use of CD10 and Pax 8 together facilitate primary diagnosis of RCC when tissue available is limited.